Temporal development of hull-fouling assemblages associated with an Antarctic supply vessel - Lee, J.E.; Chown, S.L. (Inter-Research 2009, 2010)
Introduction of non-native species poses one of the greatest, but least understood threats to marine biodiversity. Whilst considerable research effort has focused on vectors such as ballast water, hull fouling remains poorly understood and there is a notable lack of data concerning the temporal development of fouling communities. Here we use remote video capture techniques to assess the development and change of fouling assemblages on an Antarctic supply vessel over a 2 yr period. Assemblages were dominated by cosmopolitan species, some of which are known to be invasive. We demonstrate that whilst areas surrounded by sea-ice are at low risk of introductions from this pathway, substantial fouling assemblages are routinely transported to sub-Antarctic islands where the thermal conditions may allow their establishment. Extent of fouling assemblages, and thus the threat of invasion, may be reduced by changing the dry docking regime and minimising port layover times and in-water cleaning of submerged hull surfaces. Centre of Excellence for Invasion Biology